PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING - Mangobi, James U. L.; Maukar, Marvel G.; Poluan, Marsela M. (LPPM Politeknik Saint Paul Sorong, 2024)
This research aims to examine the difference in improving mathematical problem solving abilities in the System of Linear Equations Two Variables material for students who applied the Problem Based Learning model and students who applied the Direct Instruction model. This research uses a quasi-experimental method, with a pretest-posttest control group design. The subjects in this research were 20 students in class VIIIA as the control class and 20 students in class VIIIB as the experimental class. Both classes are homogeneous and the same. Gain data analysis using the t-test concluded that there was a difference in the increase in the mathematical problem solving abilities of SPLDV material for students who applied the Problem Based Learning model and students who applied the Direct Instruction model. The results of the analysis of the level of students' mathematical problem solving abilities that apply the problem based learning model in the experimental class can be seen from the achievement of the KKM. Where 85% of students have been able to reach the KKM, while 15% of students are still below the KKM. This shows that the application of the problem based model has a better influence on increasing students' mathematical problem solving abilities